Increased aqueous humor levels of endothelin-1 in patients with open angle glaucoma - Adam Hedberg-Buenz; Erin A. Boese; Angela W. Nyunt; Nathan C. Sears; Andrew E. Pouw; Kai Wang; John H. Fingert (BMC Ophthalmology)
Abstract Background Endothelin is a potent vasoconstrictor and contributes to the regulation of vascular perfusion. Aberrant endothelin-1 (ET-1) levels in aqueous humor have been reported across a variety of vascular diseases of the eye, including glaucoma. These findings suggest that dysregulation of ET-1 production may contribute to glaucoma pathophysiology. In this study, aqueous humor from patients undergoing ocular surgery was assayed for ET-1 abundance and related to the presence of glaucoma. Patients Open angle glaucoma patients (n=62 total) from the ophthalmology clinics of the University of Iowa Hospitals and Clinics were enrolled in this study and organized into three distinct cohorts based on their diagnostic criteria, including those with primary open angle glaucoma (POAG, n=25 patients), normal tension glaucoma (NTG, n=17 patients), exfoliation glaucoma (XFG, n=8 patients), and normal controls (n=12 patients). Methods Aqueous humor was collected intraoperatively from patients undergoing surgeries for glaucoma (including minimally invasive glaucoma surgeries, trabeculectomy, or glaucoma drainage device implantation) for samples in the glaucoma cohorts and cataract extraction for those in the control cohort. Aqueous humor was assayed by ELISA to measure and compare ET-1 abundance between the glaucoma cohorts and control cohort. ET-1 levels were also analyzed with linear regression to control for the covariates of age and sex. Results ET-1 was significantly elevated in the aqueous humor of patients in the POAG (mean ± SD: 7.8 ± 5.1 pg/mL; p = 0.002) and NTG cohorts (6.1 ± 3.0 pg/mL; p = 0.030) compared to the control (4.0 ± 1.9 pg/mL). No significant difference in aqueous ET-1 was detected in the XFG cohort (6.2 ± 4.5 pg/mL; p = 0.230) compared to the control. Significantly higher ET-1 levels were detected in a merged grouping of all glaucoma cohorts (POAG, NTG, XFG) relative to controls (p = 0.021). Analysis of covariance indicated neither age nor sex was associated with ET-1 level (p = 0.60 and p = 0.27), respectively. Controlling for age and sex had minimal influence on the comparison of ET-1 levels in the POAG versus control cohort (p = 0.018) and nominal influence on the comparisons between the NTG (p = 0.089) or XFG cohort (p = 0.15) relative to the control. Conclusions Elevated ET-1 in aqueous humor was associated with POAG and NTG compared to controls amongst cohorts of patients at the University of Iowa. These data suggest that dysregulation of vascular perfusion may have a role in the pathophysiology of POAG. The analyses of NTG and XFG samples were limited by the relatively small sample sizes.